Preparation and characterization of Kenaf derived heterogeneous catalyst for esterification reaction - Subramaniam K.; Pua F.-L.; Palanisamy K.; Nomanbhay S.M. (Association for Computing Machinery, 2023)
Biodiesel; Bioinformatics; Catalyst activity; Catalysts; Esterification; Esters; Hemp; Kenaf fibers; Metals; Oxides; Scanning electron microscopy; Spectrometers; Transition metal compounds; Transition metals; Tungsten; Tungsten compounds; X ray diffraction; Energy dispersive spectrometers; Esterification reactions; Kenaf; Solid acid catalysts; Transesterification reaction; Transition-metal oxides; Tungsten oxide; Wet impregnation method; Fatty acids; Calcination; Catalysts; Esterification; Kenaf; Transition Metals